1988
DOI: 10.2166/wst.1988.0019
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Chlorophenols and Chlorolignins from Bleaching Effluent by Combined Chemical and Biological Treatment

Abstract: Organic matter from spent bleaching effluents (from chlorination (C) or extraction (E) stages, or a mixture of both) was effectively precipitated as a water insoluble complex with polyethyleneimine (polyimine). Precipitation was performed in a pilot unit operating automatically. The colour, chemical oxygen demand (COD), and adsorbable organic halogens (AOX) were reduced in the C-effluent by up to 92%, 65%, and 84%, respectively. Regarding the E-stage effluent, reduction was up to 76% for colour, 70% for COD, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Laccases can also contribute to such an aim, assisting in certain processes during the manufacture of new value-added products. For instance, laccases have been typically applied in the pulp and paper industry (1) for pulp bleaching, removing the residual lignin responsible of pulp color [71], (2) for controlling pitch deposits that reduce pulp quality [75], or (3) for detoxification of bleaching effluents rich in phenolic compounds [139]. Laccases have been also evaluated for the synthesis of new materials and products from lignocellulosic feedstocks.…”
Section: Laccases For Detoxification and Delignification In A Lignocementioning
confidence: 99%
“…Laccases can also contribute to such an aim, assisting in certain processes during the manufacture of new value-added products. For instance, laccases have been typically applied in the pulp and paper industry (1) for pulp bleaching, removing the residual lignin responsible of pulp color [71], (2) for controlling pitch deposits that reduce pulp quality [75], or (3) for detoxification of bleaching effluents rich in phenolic compounds [139]. Laccases have been also evaluated for the synthesis of new materials and products from lignocellulosic feedstocks.…”
Section: Laccases For Detoxification and Delignification In A Lignocementioning
confidence: 99%
“…Laccases can also contribute to such an aim, assisting in certain processes during the manufacture of new value-added products. For instance, laccases have been typically applied in the pulp and paper industry (1) for pulp bleaching, removing the residual lignin responsible of pulp color [71], (2) for controlling pitch deposits that reduce pulp quality [75], or (3) for detoxification of bleaching effluents rich in phenolic compounds [139]. Laccases have been also evaluated for the synthesis of new materials and products from lignocellulosic feedstocks.…”
Section: Laccases For Detoxification and Delignification In A Lignocementioning
confidence: 99%
“…Bollag et al (1988) concluded that the ability of laccase to detoxify a solution containing phenols appears to be function of the compound being treated, the source of the enzyme and other environmental factors. Laccase has also been cited as a possible candidate for the treatment of bleaching plant effluent (Milstein et al, 1988;Lankinen et al, 1991). In a study on the removal of chlorophenols and chlorolignins from bleaching effluents by precipitation, Milstein et al (1988) reported that laccase could polymerize low-molecular-mass phenols, thereby facilitating their removal by reaction and precipitation with polyethyleneimine.…”
Section: (A) Aromatic Pollutantsmentioning
confidence: 99%
“…Laccase has also been cited as a possible candidate for the treatment of bleaching plant effluent (Milstein et al, 1988;Lankinen et al, 1991). In a study on the removal of chlorophenols and chlorolignins from bleaching effluents by precipitation, Milstein et al (1988) reported that laccase could polymerize low-molecular-mass phenols, thereby facilitating their removal by reaction and precipitation with polyethyleneimine. Royer et al (1991) noted that intracellular enzymes (not identified) of the fungus Coriolus versicolor had some effect on effluent decolorization.…”
Section: (A) Aromatic Pollutantsmentioning
confidence: 99%